Case Report of Low Virulence Francisella tularensis Presented as Severe Bacteremic Pneumonia. Issue 19 (May 2016) - Su, Ting-Yi; Shie, Shian-Sen; Chia, Ju-Hsin; Huang, Ching-Tai
Abstract : Abstract: Tularemia is a zoonotic infection seen primarily in the Northern Hemisphere. It is caused by the bacteria Francisella tularensis . Although the ulceroglandular form of the disease is the more common manifestation of infection, F tularensis is known to cause pneumonia. F tularensis has two predominant subspecies, namely subsp. tularensis (type A) and subsp. holarctica (type B). Type B tularemia is considered to be much less virulent than type A and barely caused lethal disease and pneumonia. We reported a case with a 68-year-old man immune-compromised patient diagnosed with bacteremic pneumonia engendered by type B tularemia with initial presentation of high fever, pneumonia with pleural effusion; the diagnosis was performed using 16S rRNA gene sequence analysis. The patient's fever, pneumonia, and pleural effusion were resolved with appropriate antibiotics for tularemia. This case involving severe bacteremic pneumonia in an immune-compromised patient is rare. This case suggests that low virulence F tularensis should be included in the differential diagnoses of bacteremic pneumonia for endemic tularemia.